Structural remains at the early mediaeval fort at Raibania, Orissa. (13th November 2013) - Sen, Bratati
The fortifications of mediaeval India occupy an eminent position in the history of military architecture. The present paper deals with the preliminary study of the structural remains at the early mediaeval fort at Raibania in the district of Balasore in Orissa. The fort was built of stone very loosely kept together. The three-walled fortification interspersed by two consecutive moats, a feature evidenced at Raibania, which is unparallel in the history of ancient and mediaeval forts and fortifications in India. Several other structures like the Jay-Chandi Temple Complex, a huge well, numerous tanks and remains of an ancient bridge add to the uniqueness of the Fort in the entire eastern region.